PENINGKATAN HASIL BELAJAR SISWA MATERI PASSING SEPAK BOLA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DI KELAS IV B SDIT INSAN KAMIL SIDOARJO - PERMATA WITIYA SARI, DWI (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Physical education is a complex subject since it develops the cognitive, affective and psychomotor aspect. In physical education, the learning achievement was influenced by the strategy and the lesson plan which were conducted by the teacher as the model in the learning process. Therefore, in improving the students' achievement, teacher needed to introduce a learning method which could create a fun and conducive atmosphere. The physical education in Insan Kamil Sidoarjo was good. Insan Kamil had sufficient facilities for physical education but for the soccer properties especially the soccer of female students, there were found some difficulties. The teacher also found difficulty in choosing the appropriate model. It hindered the learning process. As the result, it decreased the students' motivation that effected the students' achievement. The aim of this study was to examine the effectiveness of the Students' Team Achievement Division (STAD) method in improving the students' achievement in soccer passing in class IVB of SDIT Insan Kamil Sidoarjo. The subject of this study was thirty students of class IVB in SDIT Insan Kamil Sidoarjo. This study was a kind of classroom action research which had two cycles, every cycles had four sequences, those are (1) plan, (2) do, (3) observation, and (4) reflection. The data were collected through observation and test. The observation data of teacher's activity were based n the presentation. The result of the study depicted that the result of the observation had an improvement at the pre learning process. In the cycle 1, the presentation was 58, 26%, in the cycle 2, the presentation was 62,54%, and the average of the two cycles was 60,40%. Next, in the while learning process, presentations of cycle 1 was 93, 02%, cycle 2 was 99, 32%, and the average of those two cycles was 96,17%. Next at the post learning process, the presentation of cycle 1 was 90, 14%, the cycle 2 was 94, 39% and the average of those two cycles was 92, 27%. The students' achievement had a progress as 30% in which in the cycle 1 was 63, 3%. Based on the result of this study, there was found that there was an improvement of students' achievement through cooperative learning with Student teams Achievement Standard (STAD) type. It is suggested for teachers to try the attractive and interesting method. One of the attractive methods is cooperative learning method with “Student Teams Achievement Division (STAD)” type to improve students' achievement. Keywords: Students' achievement, Student Teams Achievement Division (STAD)